The impact of the public library as a children’s reading resource - ATHUKORALAGE WATHSALA VEENADARI ATHUKORALA (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This research was carried out in the Colombo Metropolitan Area of Sri Lanka to evaluate the public library as a reading resource for children in that region.Method: The case study for this research was decided to be the Colombo Public Library in Sri Lanka, and the research was conducted using the survey method. Participants in the study were children younger than 14 years old who were attendees of the Colombo Public Library in Sri Lanka. The population was divided into different strata, and a nonprobability sampling technique was used to choose which samples to take. The survey’s data collection was accomplished through the use of a questionnaire in addition to structured interviews.Findings: Based on the results, the children’s library should be placed where children can quickly get to it. This children’s library was frequented by many seventh- and ninth-graders. It’s safe to assume that most school-aged children in the Colombo Metropolitan Area regularly visit the children’s library. The children’s library does not offer standard services such as interlibrary loans, documentation, government publications, or audiovisual services. An uneven number of Sinhala, Tamil, and English books are available at the library. Although magazines are few and far between, their information, intelligence, and appreciation are too advanced for children under 14. The lack of Tamil and English-language newspapers for readers is one of the collection’s most serious flaws. It prevents children from learning to be good people and succeeding in school.Implications/Novel Contribution: The Colombo Public Library, which aims to encourage young people to develop healthy reading habits, can use this analysis to improve the quality of library services they provide to young people. Any library can use the information to serve its patrons better, and new children’s library development schemes can be formulated with the information in mind.